PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS LINGKUNGAN TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA SISWA - Kadek Ari Dwiarwati; Ni Nyoman Lisna Handyani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aims to determine the magnitude of the influence of environment-based contextual learning models on the interests and outcomes of student mathematics learning. This research is a quasi-experimental study with the design of The Posttest-Only Control-Design Group. The study population was all fifth grade students of SD Negeri 5 Bunutan. The sample is determined by group random sampling technique. The sample in this study amounted to 42 people. Data on students' learning interest were collected by questionnaires and learning outcomes using multiple choice tests. Data were analyzed using MANOVA (multivariate Analysis of Variance) assisted by SPSS 17.00 for windows. The results of the study show that: First, there is a significant difference in learning interest between students who study with environment-based contextual learning and students who learn with conventional learning models in fifth grade students at SD Negeri 5 Bunutan. Second, there are significant differences in science learning outcomes between students studying with environment-based contextual learning and students learning with conventional learning models in fifth grade students at SD Negeri 5 Bunutan. Third, Simultaneously there are significant differences in learning interest and mathematics learning outcomes between students who study with environment-based contextual learning and students who learn with conventional learning models in fifth grade students at SD Negeri 5 Bunutan.